Peran Fintech dalam Pengembangan Layanan Keuangan Syariah di Pasar Global - Abdi Ma'rifin Sugeha; Sri Dewi Yusuf (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to analyze the role of financial technology (fintech) in the development of Islamic finance services in the global market. With the rapid growth of digital technology, fintech offers innovative solutions that can enhance accessibility, efficiency, and financial inclusion, while creating new products that adhere to Islamic principles. Despite its significant potential, the implementation of fintech in the Islamic finance sector faces several challenges, such as inconsistent regulations across countries, differing interpretations of Islamic principles, and low levels of financial literacy among the public. This research employs a qualitative approach using literature review, interviews with industry experts, and surveys of Islamic fintech users to identify the opportunities and challenges present. The findings reveal that fintech plays a crucial role in expanding access to Islamic finance, particularly in developing countries, but it requires supportive policies and collaboration between governments, financial institutions, and the technology sector to overcome these challenges. The study suggests increasing financial literacy on Islamic finance and developing clear regulations to allow Islamic fintech to thrive in the global market.